2022
DOI: 10.31548/animal.13(3).2022.7-13
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different concentrations of taro paste on the sensory characteristics of poultry meat sausages

Abstract: Sausage products have a high fat content, which is not the most useful property for a sausage. The purpose of the study is the development of low-fat, nutritionally balanced sausage products. The object of the study was poultry sausages. The subject of research: changes in the quality characteristics of poultry sausage products conditioned by the use of different doses of taro puree, potato starch, and spices. Research methods: physical and chemical properties (moisture, pH, cooking losses, emulsion stability)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Sucu and Yıldız-Turp (2018) As a result of their studies using nitrite and red beet powder in sucuk, found that there was no significant difference between the residual nitrite contents of the samples at the end of the storage period. Feifei et al (2022) suggest that in the industrial application stage, it will be possible to reduce the amount of nitrite used when natural colorants are mixed with nitrite. Lipid oxidation is one of the most important changes during meat products storage and production.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Sucu and Yıldız-Turp (2018) As a result of their studies using nitrite and red beet powder in sucuk, found that there was no significant difference between the residual nitrite contents of the samples at the end of the storage period. Feifei et al (2022) suggest that in the industrial application stage, it will be possible to reduce the amount of nitrite used when natural colorants are mixed with nitrite. Lipid oxidation is one of the most important changes during meat products storage and production.…”
Section: Chemical Analysismentioning
confidence: 99%